Molecular Marker Based Characterization and Genetic Diversity Analysis of Rice Using SSR and RAPD - Khan, A. Q.; Huq, H.; Sarker, M. S. A. (International Journal of Bio-resource and Stress Management, 2015)
Twenty diverse rice germplasm were used to estimate genetic diversity using five microsatellites (SSR) and five randomly amplified polymorphic DNA (RAPD) markers. A total of 33 clear and repeatable bands were scored from RAPD markers and 33 alleles were detected from SSR primer pairs. Average polymorphic information content (PIC) value across the SSR alleles was 0.789 and average polymorphism for all microsatellite markers was 100%. Polymorphism level revealed by RAPD was 93.80%. The unweighted pair group method of arithmetic means (UPGMA) dendrogram on Nei’s genetic distance based on SSR markers clubbed germplasms into three clusters: Binadhan-5, Binadhan-6, Iratom-24, BRRI Dhan 37 and BRRI Dhan 36 in cluster 1; TNDB-100, Binashail, Chini Shagor, BRRI Dhan 41, RD-2586, Jongli Boro, BRRI Dhan-40 and Kalo Bhog formed cluster 2; and Dhol Kochuri, BINA Dhan-4, BRRI Dhan 38, Y-1281, Baowi Jhak, BRRI Dhan 32 and Kala Jira formed cluster 3. The UPGMA dendrogram on Nei’s genetic distance based on RAPD markers clustered germplasms into three clusters: BRRI Dhan 37, Iratom-24, BRRI Dhan 36, Binashail, RD-2586, BRRI Dhan 32, TNDB-100, BRRI Dhan 40 and Kala Jira were grouped in cluster 1; BRRI Dhan 38, BRRI Dhan 41, Chini Shagor, Baowi Jhak and Kalo Bhog were grouped in cluster 2; and Jongli Boro 581, BINA Dhan-4, BINA Dhan-5, BINA Dhan-6, Y-1281 and Dhol Kochuri were grouped in cluster 3. Both SSR and RAPD markers revealed BINA Dhan-5 and BINA Dhan-6 with lowest genetic diversity between them. SSR analysis showed more definite separation of clusters of genotype indicating a higher level of efficiency of these markers in determining relationships between germplasms than RAPD markers.